Examining Factors Influencing Customer Loyalty in the Electronic Product Market: Strategies for Enhancing Brand Loyalty - Liem Gai Sin; Ng Wei Chien; Gong Chongya; Li Qingyu; Hamaad Nisar Rathi; Zhou Tao; Amrithaa Poovendren; A.J. Ali; Daisy Mui Hung Kee (AIBPM Publisher, 2025)
This study integrates Oliver’s four-stage loyalty model to examine the influence of technological innovation, cultural adaptability, and personalized customer experiences on cognitive, affective, conative, and action loyalty. The study employs a mixed-method research design, incorporating both quantitative and qualitative approaches, with Huawei as the focal case study. A non-probability convenience sampling technique was used to select 150 respondents from diverse demographics. Data collection involved structured surveys and semi-structured interviews, with survey items measuring brand image, brand quality, customer satisfaction, social media interaction, and localization perception on a five-point Likert scale. Regression analysis results indicate that social media interaction (? = 0.648) and customer satisfaction (? = 0.191) significantly enhance public image, supporting H3 and H4. However, brand image and brand quality show no significant effect, leading to the rejection of H1 and H2. Additionally, localization perception strongly influences sustainability perception (? = 0.664), while brand quality has a moderate impact (? = 0.289). These findings highlight the pivotal role of digital engagement and localized strategies in fostering customer loyalty. The study offers actionable insights for electronic brands to enhance global market positioning and sustain competitive advantage.